Information systems analysis & design Alpha Business Agency - Anore, Romulo S.; de Guzman, Joel A.; Ruiz, Jose T. III.; Tanpho, Jurgen C. (Diliman, Quezon City College of Engineering, 1986)
The site in consideration is an Accounting and Business Agency with a hundred or so clients. The agency assists its clients in government-related transaction, specifically in the accomplishment and filing (includes payment) of income taxes, licenses, SSS and HDMF/Pag-Ibig contributions, patents, and other assorted legal procedures. In the accomplishment of these tasks, the agency has a workforce of 6 employees aside from the 2 owners who also serve as mangers. Of the tasks mentioned above, the most voluminous and frequent of these operations are the filing of SSS and HDMF contributions, since these operations occur monthly. Clients of the agency have between 5 to 100 employees, with 30 as the average. Thus, there are about 3000 individual whose accounts are being handled. Since this is a repetitive procedure, data on employees (name, address, SSS no., etc.) are kept on record by the agency. Data needed to be obtained from employees on a quarterly basis are the actual salaries of each employee of the previous 3 months. This is for the purpose of calculating how much contribution each employee should make, since this is based on a percentage of monthly income. The agency processes and sends the monthly forms (SSS and HDMF) to the government offices. Contributions are based on the average estimated employee salaries during the past 3 months. In addition, the agency pays for the contributions and bills the client for the amount including the service charge. Every 3 months, the agency submits quarterly collection lists together with the regular monthly forms. Data in these quarterly forms include the actual employee salaries during the past 3 months. Thus, the actual amount of contributions for the past 3 months can be contributed. Any difference in the amount remitted and the amount to be paid is then resolved through a deduction and/or an addition to the payment during the next month. The frequency and volume of recall of stored information is of a magnitude such that computerization is quite feasible. At present, the monthly salary per employee of such client is obtained by phone, contributions calculation, and all of this together with other pertinent data is typed for each employee on the forms provided. This is done twice, once for the SSS and the other for the HDMF contributions. To complicate matters the deadline for filing contributions is on the 10th of the succeeding month. This means at most 8 working days to do all of these preparations. One must also bear in mind that this operation is carried out in addition to the day-to-day operations. Hence, management is considering computerization of this aspect of their operations only in their short-range plans. This is needed to eliminate the necessity of having several employees competing for one computer unit or having several units, an option management ruled out for the immediate future due to the large cash outlay involved.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: Alpha Business Agency; Information organization; Information retrieval; Information resources management